Individual and Organizational Variables, and Work-Related Behaviors: Basis for Faculty Development Model - Dangan, Shirley (JPAIR Institutional Research, 2022)
The study aimed to derive a faculty development model based on the interrelationships of individual and organizational variables and work-related behaviors. It involved two-hundred four or 69% of the permanent faculty of Palawan State University. A modified questionnaire adapted from western studies with Cronbach’s alpha of 0.91 measured the respondents’ levels of commitment, job satisfaction, citizenship behavior, and perceptions of support, climate, and justice in the university. Statistical analysis revealed that perceived organizational climate predicts commitment, citizenship behavior, and job satisfaction, while perceived support and justice predict job satisfaction. The derived model may guide administrators in formulating policies in the university that would motivate faculty members to improve their performance and engender their sense of obligation to contribute to the accomplishment of the goals of the university. Faculty members who experienced job satisfaction, and perceived higher levels of support, ultimately become committed to their teaching, research, and community service functions. The faculty development model suggests that promoting motivation and hygiene factors in the university will actualize the norms of reciprocity between the university and its faculty. Thus, it is beneficial to foster activities in the university from which the faculty feel a favorable organizational climate, support, and justice.